City growth and its impact on residential problems: A case study in the city of Jakarta - Puji Arifin; Didin Muhafidin; Ramadhan Pancasilawan (Journal of Community Service and Empowerment, 2024)
This study aims to examine housing and settlement problems, especially in the Jakarta area as a result of population growth which has caused a very large population by identifying the number of housing needs and housing deficits. This study takes the object of the city of Jakarta as a case study and focuses on the housing sector which includes 2731 residential neighborhoods (RW) where the city occupies an area of 664.01 km2. Studies show the cause of the problem is caused by relatively stable city growth with a growth rate of around 1% over the past 20 years, which is reflected in the number of families, which amount to 3,627,111 families, with a housing density of 5462 families/km2, living in 2,242,163 housing units. The findings show that another cause is the spread of slum settlements in the city, which total 445 RWs, which means 16.30% of the total RWs. The results of the research show that so far, the problem has not been resolved.